THE IMPLEMENTATION OF GREEN ENERGY POLICY IN THE NORDIC COUNTRIES IN TERM OF ENERGY SECURITY: POLITICAL AND REGIONAL COOPERATION APPROACHES (International Conference on Social and Islamic Studies, 2021)
This study aims to analyse the political strategies and policies implemented by Nordi ccountries, both nationally and in the context of regional cooperation, in addressing to issues of energy security through the transition to green energy actions. Government of Nordic countries have succeeded in demonstrating a model of green energy policy at national and regional levels that is considered effective by many European countries, without having a significant burden on their economic performance. Therefore, it is not surprising that many countries have followed the steps taken by Nordic governments, especially through accommodative policies and regional cooperation by promoting openenergy markets. Through mixed qualitative-quantitative research method, it can be shown that regional open market on energy supply and economic incentives for the development of renewable energy are key policies on achieving sustainability in green energy production in the Nordic region. While using qualitative methods, this study demonstrates the effectiveness of political actions and regional cooperation in energy sector as the most effective strategy in achieving energy security, which many other regions in the world are trying to follow.